Effect of orofacial myofunctional exercise using an oral rehabilitation tool on labial closure strength, tongue elevation strength and skin elasticity - Ibrahim, F.; Arifin, N.; Rahim, Z.H.A. (2013)
Purpose This paper reports the effects of orofacial myofunctional exercise using an oral cavity rehabilitation device on physiological parameters that include labial closure strength, tongue elevation strength, and the right and left facial skin elasticity. Subjects Seventeen females aged forty years old and above were initially recruited for this study. Thirteen performed the exercise for 14 weeks, and only 11 subjects continued the exercise for another 10 weeks. Methods Subjects were instructed to perform an orofacial myofunctional exercise using an oral rehabilitative device for three minutes, for four times a day. The non-parametric Wilcoxon test was conducted to examine the significance of physiological parameters induced by the orofacial myofunctional exercise. The measurements of the physiological parameters were carried out weekly for 14 weeks and 24 weeks after the intervention for 13 and 11 subjects, respectively. Results The findings showed that there were significant improvements in the median values of all parameters before and after performing the orofacial myofunctional exercise for 14 weeks or more. Conclusion These results suggest that the orofacial myofunctional exercise can be regarded as a potential non-invasive therapy for improvements of the labial closure strength and tongue elevation strength, which indirectly provide support for the facial tissue, and enhances facial skin elasticity.